Answer:-
Let u(x,t) = X(x)T(t)
Substituting u back into equation and dividing by X(x)T(t)
"\\frac{X'}{X}+1=\\frac{T'}{T}"
Since the right hand side depends only on x and the left hand side only on t, both sides are equal to some constant value −C. Thus,
"\\frac{X'}{X}+1=-C,\\ \\ \\ \\ \\frac{T'}{T}=-C"
From this ODE: X(x) = Ae-(C+1)x, T(t) = Be-Ct , u(x,t) = De-(C+1)x-Ct (A,B,C,D are arbitrary constants)
From initial condition u(x,0)=4e–3x => De-(C+1)x = 4e–3x => D=4, C=2
Therefore the solution is u(x,t) = 4e-3x-2t
Comments
Leave a comment